Between Development and Democracy: A Comparative Analysis of Neo-Developmentalism in Indonesia and Singapore - Yusa Djuyandi; Luis Fiska Rahayu; Herry Soesanto (Yayasan Sembilan Pemuda Indonesia, 2026)
This article provides a comparative analysis of developmentalism and neo-developmentalism in Indonesia and Singapore, two Southeast Asian states with divergent political systems but shared development aspirations. While Singapore is widely recognized as a model developmental state, Indonesia under President Joko Widodo has been characterized as adopting a neo-developmentalist approach. This study asks: what are the key preconditions for successful developmentalism, and what are its political implications in these two contexts? Using a qualitative, comparative case study design based on secondary sources, we find that Singapore’s success rests on prior, deep bureaucratic reforms including anti-corruption measures and meritocracy that enabled effective state intervention. In contrast, Indonesia’s neo-developmentalism prioritizes debureaucratization and deregulation (e.g., the Omnibus Law), reflecting a stronger neoliberal influence. Both countries, however, show a similar consequence: the subordination of civil liberties and democratic rights to developmental goals. The article concludes that pre-conditions matter more than policy slogans, and that the trade-off between development and political freedom remains unresolved in both models.